2020
DOI: 10.3390/nu12092866
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients, Diet, and Other Factors in Prenatal Life and Bone Health in Young Adults: A Systematic Review of Longitudinal Studies

Abstract: Optimizing skeletal health in early life has potential effects on bone health later in childhood and in adulthood. We aimed to evaluate the existing evidence that maternal exposures during pregnancy have an impact on the subsequent bone health among offspring in young adults aged between 16 and 30 years. The protocol is registered in the International Prospective Register of Systematic Reviews (PROSPERO) (ID: CRD42019126890). The search was conducted up to 2 April 2019. We included seven observational prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Several studies have specifically addressed whether maternal obesity or maternal HFD during pregnancy affects bone development in offspring, both in utero and post-partum (33).…”
Section: Effect Of Maternal Obesity and Hfd On Bone In Humansmentioning
confidence: 99%
“…Several studies have specifically addressed whether maternal obesity or maternal HFD during pregnancy affects bone development in offspring, both in utero and post-partum (33).…”
Section: Effect Of Maternal Obesity and Hfd On Bone In Humansmentioning
confidence: 99%
“…It is worth mentioning that according to some authors maternal smoking affects birth weight or weight gain later in life, and thus has an adverse indirect effect on bone parameters in offspring [65,66]. Moreover, a similar assumption was made in a recent systematic review by Jensen et al [29].…”
Section: Potential Mechanisms Of Associations Between Maternal Smoking In Pregnancy and Offspring Bone Outcomesmentioning
confidence: 65%
“…As mentioned in the study by Diogenes et al [16], infant BMD may decrease in the first months of life, which is a physiological effect, therefore the influence of maternal vitamin D supplementation in pregnancy might not be significant in the youngest children. In addition, this dependence may be supported by a recent systematic review, which reported that maternal 25(OH)D status may increase BMD in young adult offspring [29]. Another explanation is that the groups of mothers in the studies were not equal in terms of vitamin D status at the moment of enrollment to the trials.…”
Section: Ambiguity In Analyzed Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…[ 22 ] A recent Bayesian network meta-analysis and meta-regression demonstrated that vitamin D supplementation does not affect risk of fractures, while supplementation with vitamin D together with calcium may have a beneficial effect for fracture prevention. [ 23 ] High concentrations of maternal vitamin D may increase the bone mineral density for adults, [ 24 ] the vitamin D dose needs to be further confirmed. Vegetables and fruits are considered major natural sources of vitamins, which may be beneficial for bone health.…”
Section: Resultsmentioning
confidence: 99%